2016
DOI: 10.1007/s11605-016-3217-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Combined Ultrasonic and Bipolar Energy Source in Laparoscopic Surgery

Abstract: TB provides a reliable and effective hemostasis. However, ligation failure may occur. As with any kind of electrosurgery, the hot tip of the instruments bears the risk of potentially fatal thermal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Surgical smoke produced by electrocautery is composed of tissue detritus, volatile organic hydrocarbons, toluene and methyl propene and other carcinogenic particles, while aerosol particles produced by USADs contain a higher amount of cells, tissue and blood detritus 18,29. During onco-logical surgery, the presence of intact cancer cells in the smoke that in turn could spread the tumor into the abdominal cavity is a matter that is not yet well investigated 30. Although advanced USADs generate less surgical aerosol, it impairs the visibility during laparoscopy, requiring frequent cleaning of the scope to remove the adhering particles, frequent cleaning of the scope is required, affecting safety and surgical time 6,25,31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical smoke produced by electrocautery is composed of tissue detritus, volatile organic hydrocarbons, toluene and methyl propene and other carcinogenic particles, while aerosol particles produced by USADs contain a higher amount of cells, tissue and blood detritus 18,29. During onco-logical surgery, the presence of intact cancer cells in the smoke that in turn could spread the tumor into the abdominal cavity is a matter that is not yet well investigated 30. Although advanced USADs generate less surgical aerosol, it impairs the visibility during laparoscopy, requiring frequent cleaning of the scope to remove the adhering particles, frequent cleaning of the scope is required, affecting safety and surgical time 6,25,31.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that inhalation of surgical smoke affects the health of surgeons 32,33. Therefore, it is recommended that surgical smoke should be removed and filtered during open and endoscopic procedures, as well prior to removing cannulas and trocars 30,32,33…”
Section: Discussionmentioning
confidence: 99%
“…The learning curve of residents for LA depends on the infrastructure of hospitality and surgical training. [ 6 7 8 ] There are many controversies in literature for minimal case or duration of experience in laparoscopy and prior experience of open appendectomy for safe LA; therefore, this study has been done. [ 9 10 ] This study aimed to determine the feasibility of safe LA performed by junior residents.…”
Section: Introductionmentioning
confidence: 99%
“…1 Their use has been broadly reported for secondary hemostasis or cutdown dissection in different specialties, such as general surgery, dermatology, and gynecology. [2][3][4] However, such modalities have been associated with extensive thermal injury of adjacent tissue that prohibits their use in dissection near sensitive neurovascular anatomic structures, especially during specific vascular surgery procedures. 1,5 Carotid endarterectomy (CEA) remains a vascular surgery procedure that demands precision and surgical skills.…”
mentioning
confidence: 99%